(untitled) (Revista Apotheke, 2024)
This article, based on a Doctoral research in Education, narrates the processes of a proposal for aesthetic education for/with teachers of Early Childhood Education, carried out amid the COVID-19 pandemic. The proposal, named “Multiple gazes: artistic and poetic studio”, developed through social networks, which used a digital media device (podcast), was based on the conception of museum as a space of knowledge and training, in (auto)biographical and life story approaches and in studies on cultural mediation and teacher training. The investigation, in a movement of dialog between school and art museum, started from listening to Early Childhood Education teachers who claimed opportunities for aesthetic training. The research showed that weaving virtual networks with teachers, in dialog with works of art from the collection of a museum, can be one of the paths.